Bridging the Strategy Execution Gap of Designing Intelligent Talent Acquisition Systems Using Enterprise Modelling and Simulation. Issue 6 (3rd June 2023) - Fayoumi, Amjad; Loucopoulos, Pericles
ABSTRACT: The development of modern intelligent systems poses numerous challenges in their strategic alignment and their effectiveness to a greater extent. Enterprise modelling emerged as a significant paradigm for holistic and systematic enterprise analysis and design. We develop a multi-view approach based on enterprise modelling and simulation that bridges the strategy execution gap between talent acquisition processes and the underlying intelligent information systems design. The approach integrates a set of techniques and tools that are rooted in the conceptual modelling paradigm. We demonstrate the value of the proposed approach in a case study, and then discuss its practical and theoretical implications.